Two types of potassium channels in murine T lymphocytes (The Rockefeller University Press, 1987)
The properties of two types of K+ channels in murine T lymphocytes are described on the basis of whole-cell and isolated-patch recordings using the gigohm-seal technique. Type l (standing for "lpr gene locus" or "large") channels were characterized mainly in T cells from mutant MRL/MpJ-lpr/lpr mice, in which they are present in large numbers. Type n ("normal") K+ channels are abundant and therefore most readily studied in concanavalin A-activated T cells from four strains of mice, MRL-+/+, CBA/J, C57BL/6J, and BALB/c. Type l channels, compared with type n, are activated at potentials approximately 30 mV more positive, and close much more rapidly upon repolarization. Type l channels inactivate more slowly and less completely than type n during maintained depolarization, but recover from inactivation more rapidly, so that little inactivation accumulates during repetitive pulses. Type l channels have a higher unitary conductance (21 pS) than type n (12 pS) and are less sensitive to block by external Co++, but are 100-fold more sensitive to block by external tetraethylammonium (TEA), with half- block of type l channels at 50-100 microM TEA compared with 8-16 mM for type n. TEA blocks both types of channels by reducing the apparent single channel current amplitude, with a dose-response relation similar to that for blocking macroscopic currents. Murine type n K+ channels resemble K+ channels in human T cells.